Notch signaling induces either apoptosis or cell fate change in multiciliated cells during mucociliary tissue remodeling - Tasca, Alexia (Dev Cell, 2021)
Multiciliated cells (MCCs) are extremely highly-differentiated, presenting >100 cilia and basal bodies. Therefore, MCC fate is thought to be terminal and irreversible. We analyzed how MCCs are removed from the airway-like mucociliary Xenopus epidermis during developmental tissue remodeling. We found that a subset of MCCs undergoes lateral line-induced apoptosis, but that the majority coordinately trans-differentiate into Goblet secretory cells. Both processes are dependent on Notch signaling, while the cellular response to Notch is modulated by Jak/STAT, Thyroid hormone and mTOR signaling. At the cellular level, trans-differentiation is executed through loss of ciliary gene expression including foxj1 and pcm1, altered proteostasis, cilia retraction, basal body elimination as well as initiation of mucus production and secretion. Our work describes two modes for MCC loss during vertebrate development, the signaling regulation of these processes, and demonstrates that even cells with extreme differentiation features can undergo direct fate conversion.